Proteomic study on the stability of proteins in bovine, camel, and caprine milk sera after processing. (April 2016) - Zhang, Lina; Boeren, Sjef; Smits, Marcel; van Hooijdonk, Toon; Vervoort, Jacques; Hettinga, Kasper
Abstract: Milk proteins have been shown to be very sensitive to processing. This study aims to investigate the changes of the bovine, camel, and caprine milk proteins after freezing, pasteurization (62 °C, 30 min), and spray drying by proteomic techniques, filter-aided sample preparation (FASP) and dimethyl labeling followed by liquid chromatography–tandem mass spectrometry (LC–MS/MS). A total of 129, 125, and 74 proteins were quantified in bovine, camel, and caprine milk sera, respectively. The milk serum protein content decreased significantly after freezing, pasteurization, or spray drying, which can be ascribed to the removal of protein aggregates by the pH adjustment and ultracentrifugation during sample preparation. Some of the immune-related proteins were heat-sensitive, such as lactoferrin (LTF), glycosylation-dependent cell adhesion molecule 1 (GLYCAM1), and lactadherin (MFGE8), with losses of approximately 25% to 85% after pasteurization and 85% to 95% after spray drying. α-Lactalbumin (LALBA), osteopontin (SPP1), and whey acidic protein (WAP) were relatively heat stable with losses of 10% to 50% after pasteurization and 25% to 85% after spray drying. The increase of some individual proteins in concentration after freezing may be caused by the proteins originating from damaged milk fat globules and somatic cells. GLYCAM1 decreased significantly after pasteurization in bovine and camel milk but this protein is relatively stable in caprine milk. In conclusion, milk proteins changed differently in concentration after different processing steps, as well as among different species. Highlights: Soluble milk serum protein concentration decreased with decreased processing severity. Immune-related proteins showed high sensitivity to heat treatment. Freezing of milk, as usually done during research studies, can impact the milk proteome. The quantitative changes of milk serum proteins differed between species.